Formulación variacional de ecuaciones diferenciales parciales (2010)
This paper deals with the study of the variational method for partial differential equations concerning the existence, uniqueness and regularity of the solution. The aim of this work is to give a comprehensive description of the variational method, presenting examples from the simple second order linear elliptic partial differential equations to a most complex first order non-linear partial differential equation. Comments on the adaptability of this method to this kind of equations are given.